Siiddat ja siiddaolbmot Suoma sierralágain ja sierralágaid ovdabargguin - Labba, Oula-Antti (Sámi dieđalaš áigečála, 2024)
Dán artihkkalis dutkkan siiddaid ja siiddaolbmuid sajádaga Suoma iehčanasvuođa áigge (1917–) sierralágain ja sierralágaid ovdabargguin. Mu dutkan gažaldat lea makkár lea leamašan siiddaid, siiddaolbmuid ja sámiide mihtilmas ealáhusaid vuoigatvuođalaš sajádat dán áigodagas ja got dat oidno láhkaásaheamis ja láhkaásahanbarggus gitta otná beaivvi rádjai. Suoma iehčanasvuođa álgoáigge siiddaolbmuid riektesajádat namuhuvvui dávjá sierralágaid ovdabargguin, muhto ii dovddastuvvon ieš lágain. Sihke Sámi Parlameanta ja ovttaskas sámit geahččale maid 1970-logu loahpa bealde gitta 1990-logu álgui oažžut siiddaid sajádaga dovddastuvvot sierralágain. Dán áigodagas siiddat vuohon ihtigohte lágaid ovdabargguide, muhto eai ieš lágaide.English title: Sámi siidas and siida people in the special laws and preliminary works of laws during the Finnish independence eraEnglish abstract: My article aims to investigate the recognition of the legal status of siidas (Sámi villages) as collectives, along with their individual members, within the framework of special laws (lex specialis) and legislative preparations during the period of Finland’s independence (1917–). My research questions include: what was and is the legal status of siida and siida members in this era, how has the status changed and why. The region of focus for my research encompasses the Sámi homeland in Finland. During the initial years of Finnish independence, the legal standing of siida members were frequently mentioned in legislative proposals and other preparatory documents. However, the legislation that was enacted failed to acknowledge their status and rights. For example, the reindeer herding rights of the Sámi siida people have been extended to the descendants of Finnish settlers without a legal basis. Numerous efforts were made by individual Sámi individuals and the Sámi Parliament to seek recognition of the legal status of Sámi villages and their residents within the lex specialis.
Keywords: siiddat; siiddaolbmot; boazodoallu; guolásteapmi; meahcásteapmi; Suopma; Sámi villages; fishing; reindeer herding; hunting; legal status of siidas